Feline herpesvirus ulcerative dermatitis: an atypical case?. Issue 3 (6th April 2018) - Porcellato, Ilaria; Luciani, Luca; Marenzoni, Maria Luisa; Santagostino, Sara Francesca; Sforna, Monica; Mechelli, Luca; Brachelente, Chiara
Abstract : Background: Feline herpesvirus ulcerative dermatitis is an uncommon skin disease in cats, with a predominantly facial distribution characterized by massive infiltration of eosinophils and, occasionally, predominant neutrophils. Objective: To describe the clinical and histopathological features of a putative atypical case of feline herpesvirus dermatitis. Animal: A 10‐month‐old, intact male, European cat was presented with chronic monolateral ulcerative dermatitis with adherent crusts on the left pinna. The lesion had been present for six months and worsened after the administration of corticosteroids. Methods: Clinical and histopathological examination, immunohistochemistry, nested PCR and transmission electron microscopy (TEM). Results: Histological examination of skin biopsies showed multifocal ulcerative and necrotic lesions, involving the superficial and deep dermis covered by thick haemorrhagic and serocellular crusts. The superficial, medium and deep dermis was heavily infiltrated with mast cells and plasma cells, with a lower number of neutrophils and eosinophils. In the nuclei of some cells in the deep dermis, whose histotype was unrecognizable with routine haematoxylin and eosin stain, intranuclear eosinophilic inclusion bodies were noticed. Nested PCR and TEM supported the hypothesis of FeHV‐1‐induced dermatitis. Conclusions and clinical importance: This case is noteworthy for the infrequent location on the pinna and the atypical histopathological features of the lesion, with a predominant infiltration of mast cells and plasma cells. Our findings suggest that herpesvirus dermatitis should be listed as a differential diagnosis in case of ulcerative dermatitis when the location and histological features are atypical. Abstract : Background Feline herpesvirus ulcerative dermatitis is an uncommon skin disease in cats, with a predominantly facial distribution characterized by massive infiltration of eosinophils and, occasionally, predominant neutrophils.Objective To describe the clinical and histopathological features of a putative atypical case of feline herpesvirus dermatitis.Conclusions and clinical importance This case is noteworthy for the infrequent location on the pinna and the atypical histopathological features of the lesion, with a predominant infiltration of mast cells and plasma cells. Our findings suggest that herpesvirus dermatitis should be listed as a differential diagnosis in case of ulcerative dermatitis when the location and histological features are atypical.